2017
DOI: 10.1080/09546634.2017.1303569
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of an over-the-counter 1% colloidal oatmeal cream in the management of mild to moderate atopic dermatitis in children: a double-blind, randomized, active-controlled study

Abstract: Efficacy and safety of an over-the-counter 1% colloidal oatmeal cream in the management of mild to moderate atopic dermatitis in children: a double-blind, randomized, active-controlled study, Journal of Dermatological Treatment, 28:7, 659-667, DOI: 10.1080/09546634.2017 Purpose: The purpose of this study is to evaluate the efficacy and safety of an over-the-counter (OTC) 1% colloidal oatmeal cream versus a prescription barrier cream in children with mild-to-moderate atopic dermatitis (AD). Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…On the other hand, brief hot showers have shown itch-relieving effects in experimental studies applying heat to chronic pruritus and atopic skin (142,143). Also, lukewarm baths with colloidal oatmeal may restore skin barrier and sooth pruritus (144). Moisturisers with water and liquid paraffin base are used in soothing creams and emulsions.…”
Section: Therapy: General Principles Including Emollientsmentioning
confidence: 99%
“…On the other hand, brief hot showers have shown itch-relieving effects in experimental studies applying heat to chronic pruritus and atopic skin (142,143). Also, lukewarm baths with colloidal oatmeal may restore skin barrier and sooth pruritus (144). Moisturisers with water and liquid paraffin base are used in soothing creams and emulsions.…”
Section: Therapy: General Principles Including Emollientsmentioning
confidence: 99%
“…48 In line with this, in one double-blind, randomized, activecontrolled study, Lisante et al recently reported over-thecounter 1% colloidal oatmeal cream is as effective as a prescription barrier cream for the symptomatic treatment mild-to-moderate atopic dermatitis in children. 10 In contrast to these findings, one French prospective study found oat sensitization is higher than expected in children with atopic dermatitis. 49 These discrepancies can be partially justified by the methodological flaws in French study which used oat pollen for skin prick tests and IgE testing.…”
Section: Discussionmentioning
confidence: 83%
“…9 Oatmeal possesses potent antioxidant and antiinflammatory properties that its clinical benefits in the treatment of a variety of inflammatory dermatologic disorders such as atopic dermatitis, psoriasis, and dry skin have been shown in the previous studies. [10][11][12] The active ingredients in oatmeal consist of polysaccharides, proteins, lipids, saponins, enzymes, flavonoids, vitamins, and avenanthramides. Avenanthramides are phenolic compounds present in oats that mediate its anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies included within the systematic review mostly ranged from ''low risk'' to ''some concerns,'' with one ''high risk study'' (Fig 1, Table I). [5][6][7][8][9][10][11][12][13] The Egger's test grouped by treatment showed no bias for aloe vera (AV) or turmeric. Bias was present for green tea (GT); however, further analysis through the ''fill and trim'' publication bias technique 14 deemed no publication bias.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Eczema area and severity index in AD. One study that included 68 patients with AD examined the efficacy of treatment with CO 13 (Table III). The primary outcome measured was improvement of the eczema area and severity index score.…”
mentioning
confidence: 99%